PENGEMBANGAN BUKU SISWA TERPADU TIPE JARINGAN KERJA TERINTEGRASI PENDEKATAN ILMIAH DI SD KELAS IV - Kharisma Eka Putri (Jurnal Ilmiah Ar-Risalah: Media Ke-Islaman, Pendidikan dan Hukum Islam, 2017)
Research of the teaching material development of networked  with scientific approach was proposed to determine: the feasibility of student book developed and  students responses. To attain these objectives, it had been research that started by preparation of student books, followed by try out of the teaching material in the integrated science learning. The research was conducted on a class IV student SD Negeri1 Ngampel Kediri many as 12 students. The teaching material development model used was 4D. However, in this study was limited until to the development stage. Data collect method in this experiment is validation and questionnaire. The data of  research showed that the student book developed was feasible to use suitable with expert validation and validation of  the student book readability. The result obtained from validation of student books 3,62. Mean while, the readability of the student’s book gets a percentage of  83,33 with a very strong criterion. The results of  questionnaire analysis responses showed that students in integrated science type networked, with Scientific Approach  teaching were students responded positively to that learning.